Consumers’ Perspectives on Fintech Lending in Indonesia: Analysis of Herding Behavior and Physiological Needs - Anisa Rachmawati; Selfi Artika; Oktavia Dewi Sari Mukti (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
Financial technology is a technological innovation in financial services that is currently developing sector in Indonesia. This study focuses on fintech, which provides online loan financial services called fintech lending. The research gap on peer-to-peer lending was found in the study investigating one of the peer-to-peer lending problems and the existence of information asymmetry. Based on the research gap, this study analyzes the herding behavior of consumers as borrowers. It analyzes consumers’ perspectives as borrowers on technological innovation in peer-to-peer lending in making decisions to fulfill basic physiological needs. The study relays to descriptive qualitative research. It analyzes the social situation that leads to phenomenology. Purposive sampling and snowball sampling were used in this study. There were 31 participants involved in this study that belonged to individuals who have made online loans with the peer-to-peer lending system. A qualitative open-ended question questionnaire was used to collect the data. The finding of this study shows that as many as 70.97% of the 31 respondents use fintech lending applications from recommendations of a friend or relative. In the current phenomenon, consumers imitate people who previously used fintech lending applications. Therefore, the result is in line with the concept of Herding Behavior that respondents select to use the fintech lending application because of an invitation and recommendation from a friend or relative. In addition, most respondents aged 20-30 years who are unmarried use fintech lending applications to fulfill lifestyle needs, while respondents aged 20-40 who are married use fintech lending applications to fulfill basic and business needs.